STUDY ON THE MICROECONOMIC FINANCING DECISION - ILIE RĂSCOLEAN; ILEANA-SORINA RAKOS (Annals of the University of Petrosani: Economics)
The purpose of the action taken by the authors is to demonstrate that, in order to substantiate the financing decision within an economic entity, the starting point is the principle according to which current assets are financed from short-term sources and fixed assets - from long-term sources. The financing decision must be taken on the basis of the correlation between the costs of capital and the profitability of the financing projects. The objective of this paper is to demonstrate that the objective of an economic entity is to achieve the lowest cost of capital acquisition, under a reasonable and controllable degree of indebtedness, as demonstrated by an empirical study on the example of an economic entity in Hunedoara County. The article concludes with the authors' conclusions on the need to improve the timing of the debt collection gap and the average debt repayment period, with positive influences on net cash; increasing the profitability of the economic entity's activity through measures to optimize expenditures; ensuring financial autonomy for the entity.